2021
DOI: 10.1016/j.jhepr.2021.100325
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive lipidomics reveals phenotypic differences in hepatic lipid turnover in ALD and NAFLD during alcohol intoxication

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…In the present study, we also found that the 3 changed LPCs and 3 LPEs in response to alcohol exposure were all down-regulated. Compared with the effects on TAGs and free fatty acids metabolism, the effect of alcohol intake on LPC and LPE in liver is less well established but may be increased [ 7 , 25 ]. LPC and LPE always server as the precursors of lysophosphatidic acid (LPA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we also found that the 3 changed LPCs and 3 LPEs in response to alcohol exposure were all down-regulated. Compared with the effects on TAGs and free fatty acids metabolism, the effect of alcohol intake on LPC and LPE in liver is less well established but may be increased [ 7 , 25 ]. LPC and LPE always server as the precursors of lysophosphatidic acid (LPA).…”
Section: Discussionmentioning
confidence: 99%
“…Evidences from animal experiments have shown the complex interaction between alcohol and hepatic lipid metabolism [ 7 ]. It has been proposed that alcohol has distinct effects on different types of fatty acids, according to the carbon length and degree of unsaturation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“… 78 Ethanol increases the uptake of FAs by the liver in vivo 79 and in vitro 80 leading to intrahepatic accumulation of TGs. 81 Abstinence has been shown to reduce serum FA and LPC levels, while TGs stay elevated 82 in patients with ALD ( Table 1 ). Moreover, in several models, FA synthesis pathways are significantly upregulated in mice fed alcohol ad libitum in their drinking water.…”
Section: Lipid Alterations In Liver Diseases Associated With the Deve...mentioning
confidence: 99%
“…An overview of the study design and setup can be seen in Figure 1. Results of the primary study are reported elsewhere 17 . The 48‐hour alcohol abstinence was confirmed by measuring blood ethanol levels on the day of the investigation before the start of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Results of the primary study are reported elsewhere. 17 The 48-hour alcohol abstinence was confirmed by measuring blood ethanol levels on the day of the investigation before the start of the study. The intervention was in the form of a weight adjusted ethanol-NaCl mixture that was administered via a nasogastric tube and infusion pump.…”
Section: Investigationsmentioning
confidence: 99%